PERANCANGAN APLIKASI INVENTARISASI SUKU CADANG PERALATAN METEOROLOGI BERBASIS SISTEM OPERASI ANDROID DENGAN DATABASE SQLITE PADA SUB BIDANG INSTRUMENTASI REKAYASA PERALATAN METEOROLOGI BMKG - Muniroh, Nur; Muzayyinul Achkam, Dicki Achmad (Jurnal Teknologi dan Bisnis, 2019)
The object of this research is the sub-field of instrumentation and engineering of the Jakarta BMKG meteorological equipment. This sub-sector of instrumentation and engineering of meteorological equipment is that which provides spare parts for meteorological equipment for meteorological stations throughout Indonesia. In the inventory of spare parts in the sub-field of instrumentation and engineering of meteorological equipment, MS Excel is still used on the computer so it is not practical and cannot be carried anywhere. By using the spare parts inventory application on this android phone and with the SQLite database, it will make it easier for the spare parts inventory process and more practical and can be carried everywhere.